An overview of the regulation of influenza vaccines in the United States. Issue 5 (24th March 2016) - Weir, Jerry P.; Gruber, Marion F.
Abstract : Influenza virus vaccines are unique among currently licensed viral vaccines. The vaccines designed to protect against seasonal influenza illness must be updated periodically in an effort to match the vaccine strain with currently circulating viruses, and the vaccine manufacturing timeline includes multiple, overlapping processes with a very limited amount of flexibility. In the United States (U.S.), over 150 million doses of seasonal trivalent and quadrivalent vaccine are produced annually, a mammoth effort, particularly in the context of a vaccine with components that usually change on a yearly basis. In addition, emergence of an influenza virus containing an HA subtype that has not recently circulated in humans is an ever present possibility. Recently, pandemic influenza vaccines have been licensed, and the pathways for licensure of pandemic vaccines and subsequent strain updating have been defined. Thus, there are formidable challenges for the regulation of currently licensed influenza vaccines, as well as for the regulation of influenza vaccines under development. This review describes the process of licensing influenza vaccines in the U.S., the process and steps involved in the annual updating of seasonal influenza vaccines, and some recent experiences and regulatory challenges faced in development and evaluation of novel influenza vaccines.